Ecotourism Impacts of Old Oyo National Park on Host Communities - Abiola-Oke, Elizabeth (Journal of Geography, Environment and Planning, 2015)
Old Oyo National Park has commenced active ecotourism services based on ecology and archaeology resource. This includes, the museum at the park's administrative head office and Akoto camp display exhibits of cultural, archaeological and historical values for eco-tourists’ delight (NNPS, 2015). This research work delves into the impact of this ecotourism park on the host communities. The findings reveals that the impacts are multifaceted both positive and negative. It further revealed that though some of the locals have benefited from employment opportunities within the park, and provisions of borehole and good roads, but the challenges relating to clashes, litigations and lack of active participation or involvement of the communities in the park management activities on one hand and that involving policy clashes between the community members and the park management on the other hand are major issues militating against the development and peaceful co-existence of the park development and the host communities. Suggestions, hinging on the creation of community friendly awareness, adopting active participatory approach to park management and provision of healthy and economically viable environment for living were recommended for effective park management within the host communities.
Keywords: Ecotourism; Host community; Participation